AUTHENTICITY AND UNIQUENESS OF ASINAN BOGOR AS A DISTINCTIVE CULINARY DELIGHT OF BOGOR CITY - Putri, Ardaneswara; Ramdhani, Rafy; Rosalia, Melva; Arraniri, Fahma Faradisa; Kurnia, Insan; Rahayu, Kania Sofiantina (Home Economics Journal, 2024)
Asinan bogor, commonly known as Bogor salty pickles, represents a traditional delicacy of Bogor, Indonesia, consisting of processed vegetables and fruits consumed raw alongside various additional ingredients.  This research aims to delve into the uniqueness of asinan bogor.  The study was conducted through surveys interviews, and questionnaires administered to 40 asinan Bogor sellers in Bogor City.  Sellers unanimously recognize asinan bogor as a Bogor traditional dish.  Sellers exhibit the highest level of knowledge concerning raw materials, with history being their least familiar aspect.  While no main ingredients are obligatory, specific components hold priority, such as bean sprouts for vegetables pickled; and mango, water guava, and jicama for fruits pickled.  Mandatory seasoning ingredients include ground red chili, salt, and water.  The composition of asinan ingredients varies based on consumer preferences.  Antanan is rarely utilized as a primary ingredient, whereas salted mustard green epitomizes Chinese cuisine.  Currently, the serving of asinan bogor is predominantly in plastic packaging, deviating from on-site consumption, particularly for souvenir packaging.  The paramount uniqueness of the asinan bogor lies in the gravy.